2019
DOI: 10.1093/carcin/bgz177
|View full text |Cite
|
Sign up to set email alerts
|

Differential localization of PD-L1 and Akt-1 involvement in radioresistant and radiosensitive cell lines of head and neck squamous cell carcinoma

Abstract: Immunotherapy by blockade of the PD-1/PD-L1 checkpoint demonstrated amazing tumor response in advanced cancer patients including head and neck squamous cell carcinoma (HNSCC). However, the majority of HNSCC patients still show little improvement or even hyperprogression. Irradiation is currently investigated as synergistic treatment modality to immunotherapy as it increases the number of T-cells thereby enhancing efficacy of immunotherapy. Apart from this immunogenic context a growing amount of data indicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…This is in line with our observation of decreased disease‐free survival. Moreover, they saw a time‐dependent increase of PD‐L1 in rs cells and decrease in rr cells after irradiation 33 . It has to be assumed that cancerous tissue consists of both, rr and rs cells and this might be the explanation for the fact that we could measure no significant changes of PD‐L1 by CRT.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This is in line with our observation of decreased disease‐free survival. Moreover, they saw a time‐dependent increase of PD‐L1 in rs cells and decrease in rr cells after irradiation 33 . It has to be assumed that cancerous tissue consists of both, rr and rs cells and this might be the explanation for the fact that we could measure no significant changes of PD‐L1 by CRT.…”
Section: Discussionmentioning
confidence: 82%
“…Our review revealed no obvious consensus about the prognostic role of PD‐L1 expression (Table 2). 26‐33 Among these studies, Schulz et al were the only group to look at changes of PD‐L1 expression by radiation. They compared known radio‐resistant (rr) with radio‐sensitive (rs) cell lines and could measure high PD‐L1 expression in rr cells before radiation.…”
Section: Discussionmentioning
confidence: 99%
“…PD-L1 is mainly located on the cell membrane and in the cytoplasm, yet it is also found in the nucleus to a lesser extent. Nuclear PD-L1 is detected in many cancer tissues, including renal cell carcinomas, colorectal cancer, prostate cancer, lung cancer, and hepatocellular carcinomas [ 57 , 58 , 59 ]. Its expression is significantly correlated with tumor invasion, radioresistance, and overall survival, suggesting that nuclear PD-L1 could be a potential prognostic biomarker in cancer patients [ 57 , 60 ].…”
Section: To the Grave: From Cell Membrane To Recycling And Lysosome Degradationmentioning
confidence: 99%
“…In our studies, we explored the underlying reason behind these findings. In recent years, a growing number of studies have concluded that PD-L1 may not only have immunogenic but at the same time cell-intrinsic functions [ 23 , 24 , 38 ]. This study was conducted because we observed a confluence- and time-dependent fluctuation of PD-L1 expression in all our HNSCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we demonstrated the strong influence of PD-L1 on proliferation, migration, invasion, and survival after irradiation [ 23 ]. Furthermore, we revealed differential expression and localization of PD-L1 depending on the sensitivity to irradiation [ 24 ].…”
Section: Introductionmentioning
confidence: 99%